Students’ Performance in Cultural Text Writing Based on Situational Context and Cohesive Devices: A case study of Discourse Analysis - Sidabutar, Usman; Sahlan Tampubolon (Universitas Cokroaminoto Palopo, 2024)
This research is described to classify cohesive devices and contextualize the cohesive devices on the English Students Writing at HKBP Nommensen University Medan. There is a role that creates importance and urgency regarding the development of writing skills which can be considered a mode related to problems that often arise in writing. Classification and contextualization are polarities for determining the type of text as student writing. Research that applies qualitative methods is considered scientifically to obtain more valid results. The subjects of this study were 50 students on the sixth semester of English Education with research locations at HKBP Nommensen University, Medan. Specifically, for situational context and cohesive devices, the data were comprised to context A, context B and context C. Based on the research results, the classification of cohesive devices is found in varying amounts of student writing, but the totality of the use of Lexical Cohesion tends to be more dominant in student writing, especially in context A with 33 percent. Meanwhile, in context B the use of references accounts for 28 percent of student writing. Context becomes the prompt performance in the teaching process including cohesive devices and context formed by teacher-student interactions in the classroom